2019
DOI: 10.1186/s12872-019-1133-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic chest pain in patients presenting to an urban emergency Department in sub Saharan Africa: a prospective cohort study in Tanzania

Abstract: Background Non-traumatic chest pain (NTCP) is a common reason for emergency department (ED) attendance in high-income countries, with the primary concern focused on life threatening cardiovascular diseases. There is general lack of data on aetiologies, diagnosis and management of NTPC in Sub Sahara African (SSA) countries. We aimed to describe evaluation, diagnosis and outcomes of adult patients presenting with NTCP to an urban ED in Tanzania. Method This was a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
4
5
0
Order By: Relevance
“…The majority of patients were diagnosed with symptomatic hypertension or heart failure, two diagnoses that arguably require exclusion of ACS. Although not the focus of our study, the large numbers of ED patients we observed being diagnosed with heart failure or hypertension are consistent with what has been reported elsewhere in Tanzania [9,23], suggesting that these diseases warrant particular attention from public health officials. Less than 1% of enrolled patients received empiric treatment with aspirin, an inexpensive and widely available treatment known to reduce mortality in ACS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The majority of patients were diagnosed with symptomatic hypertension or heart failure, two diagnoses that arguably require exclusion of ACS. Although not the focus of our study, the large numbers of ED patients we observed being diagnosed with heart failure or hypertension are consistent with what has been reported elsewhere in Tanzania [9,23], suggesting that these diseases warrant particular attention from public health officials. Less than 1% of enrolled patients received empiric treatment with aspirin, an inexpensive and widely available treatment known to reduce mortality in ACS.…”
Section: Discussionsupporting
confidence: 91%
“…Chest pain was present in 6.7% of adult ED patients, more than five-fold higher than the prevalence observed elsewhere in Tanzania, and similar to the prevalence observed in EDs in Europe and the United States [5,21,22,23]. The prevalence of chest pain noted in our setting is remarkable, given the recent finding that most Tanzanian adults would not present to a hospital for chest pain [15].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[38][39][40] As a presenting complaint, abdominal pain has been described as a diagnostic challenge 34,41,42 for ED clinicians, with an array of potential causes ranging from mild to serious lifethreatening conditions 36,41,43,44 and hospital admission rates ranging between 16.5% and 36%. 36,38,44 Similarly, chest pain is frequently cited as one of the top 5 reasons for patients' presentation to the ED, 30,33,40,45 with studies between 2014 and 2019 reporting chest pain in ED cohorts representing between 1.5% and 1.82% in sub-Saharan Africa, 46,47 4.11% and 4.7% in the United States, 30,33,48 and 11% and 13% in Norway 40,45 (where EDs require general practitioner referral 45 ). Commensurate with abdominal pain, the cause of chest pain is diverse, [47][48][49] ranging from nonspecific to life-threatening conditions, with reported admission rates varying between 30.6% 48 and 89%.…”
Section: How This Is Relevant To Clinical Practicementioning
confidence: 99%